2012
DOI: 10.1088/0268-1242/27/2/024013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of indium incorporation in non- and semipolar GaInN QW structures: comparing x-ray diffraction and optical properties

Abstract: We have studied the growth of GaInN/GaN quantum wells on various polar, nonpolar and semipolar planes. From a detailed x-ray diffraction analysis, we derive the strain state and the composition of the quantum wells. The optical emission energy is obtained from photoluminescence spectra and modelled taking into account the deformation potentials and the Stark shifts. Both x-ray and optical data consistently show that indium incorporation is identical on the polar, nonpolar and semipolar planes within the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
18
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
8
18
2
Order By: Relevance
“…While they found that the photoluminescence emission energy varied by as much as 600 meV, they determined that the major contribution to the difference in emission energy between (0001) and (10-10) was the QCSE and that the red shift between the nonpolar (10-10) and semipolar (10)(11)(12) and (20)(21) QWs was due to shear and anisotropic strain affecting the valence band structure. Only for QWs grown on the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and (10-11) semipolar planes did they find that a significantly higher indium incorporation was responsible for the red shift. However, Jonen et al [22][23] found that the indium incorporation in QWs did not change within experimental error between c-, nonpolar and semipolar planes, including (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…While they found that the photoluminescence emission energy varied by as much as 600 meV, they determined that the major contribution to the difference in emission energy between (0001) and (10-10) was the QCSE and that the red shift between the nonpolar (10-10) and semipolar (10)(11)(12) and (20)(21) QWs was due to shear and anisotropic strain affecting the valence band structure. Only for QWs grown on the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and (10-11) semipolar planes did they find that a significantly higher indium incorporation was responsible for the red shift. However, Jonen et al [22][23] found that the indium incorporation in QWs did not change within experimental error between c-, nonpolar and semipolar planes, including (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 97%
“…Early work focused on the (10-1-1) GaN substrate orientation as GaInN LEDs and LDs grown on that orientation for emission in the blue and longer wavelengths showed promise [6][7]. Substantial efforts were made to perfect the growth on (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN [8][9][10][11] as indium incorporation was favored on this orientation. However, material quality degradation due to misfit dislocation generation at high indium content [12] shifted the focus to other orientations, since (20)(21) GaN was shown to be capable of incorporating sufficient indium while maintaining the crystalline quality, enabling the demonstration of the first true green GaN based lasers [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations